Implementasi Kebijakan Program Pemberdayaan Ekonomi Masyarakat Petani Rumput Laut Desa Labuhan Kertasari Kabupaten Sumbawa Barat - Zulkifli Muhadli (Universitas Batanghari Jambi, 2020)
The existence of the Seaweed Farming Community Economic Empowerment Program in Labuhan Kertasari Village, West Sumbawa Regency is motivated by qualified resources to cultivate seaweed in order to improve the economy of the community in the area. The Department of Maritime Affairs and Fisheries of West Sumbawa Regency strives to improve the economy of the seaweed farming community by exploring and empowering the potential of Labuhan Kertasari Village. The purpose of this study was to determine the implementation of policies on economic empowerment programs for coastal communities, especially seaweed farming communities in Labuhan Kertasari Village, West Sumbawa Regency. The program's policy implementation is in the form of policies in communicating between related parties and policy makers, resources, dispositions or attitudes as seen by policy makers and the bureaucratic structure applied by the local area. The objective of this program can be achieved if the implementation of the Economic Empowerment of the Seaweed Farming Community is seen from the accuracy of policies, accuracy of implementation, accuracy of the environment, accuracy of targets, and accuracy of processes. Data analysis was carried out qualitatively, both primary and secondary data, with three activities (triangulation), namely: data reduction, data presentation, verification or data conclusion. The results of this study indicate that the Department of Marine Affairs and Fisheries of West Sumbawa Regency is ready to implement the Economic Empowerment Program for the Seaweed Farming Community in Labuhan Kertasari Village. The implementation of the Economic Empowerment of the Seaweed Farming Community has been carried out well. The influencing factors are (1) the ability of a good implementer in determining policies even though there are communication obstacles between farmers and local governments, (2) clarity of information obtained by the community, (3) commitment of good implementers in implementing the community economic empowerment program. , (4) maximizing the utilization of the executor's authority to determine appropriate targets and processes.